EVALUASI KINERJA PERSEDIAAN BARANG JADI DENGAN MENENTUKAN SERVICE LEVEL BERDASARKAN FORECASTING PERMINTAAN, PENGENDALIAN PERSEDIAAN, DAN SIMULASI MONTE CARLO DI PT XYZ - Hashifah Husna (2022)
PT XYZ, a building goods retail company, does not apply structured inventory control so that stockouts and overstocks often occur for several products. In addition, the company also does not set service levels and safety stock for each of its products. Therefore, researcher evaluates the performance of inventory which aims to carry out inventory control so that the appropriate service level can be determined. Inventory is classified by sales value using the ABC Analysis method, then demand forecasting is carried out for three products, namely Besi Beton 8 from class A, Siku 30x30x3 from class B, and Stall 30/30-1.8 from class C. Then inventory control is carried out using the continuous review system method with 2 types of service levels, service level based on ABC classification and service level of 95%. Monte Carlo simulation is done to simulate future demand. From the results of the demand simualtion, a perpetual inventory simulation is carried out which results in a total inventory cost using the ABC Analysis service level method Rp1.811.038,77 with a savings of 22,72% of the initial inventory cost and an increase in inventory turnover rate of 35.63% by accelerating inventory days of supply for 26 days. The use of 95% as the service level results in a total cost of Rp1.788.680,77 with a savings of 23,67% from the initial inventory cost and increases inventory turnover rate by 38.02% by accelerating inventory days of supply for 27 days. Thus, service level of 95% is the best service level for the three products.